Furniture Design of Smart Art Classroom Based on Interactive Analysis of Intelligent Sensing and ITIAS - Bai, Yifan; Kamarudin, Khairul Manami; Alli, Hassan (Taylor and Francis Ltd., 2024)
This paper explores the design and optimization of smart art classroom furniture, addressing the evolving needs of modern art education environments. With the integration of intelligent technologies and sensor networks, the research aims to enhance the functionality, flexibility, and user experience of classroom furniture. It highlights the limitations of traditional classroom furniture and the need for adaptive, multifunctional designs that accommodate diverse learning behaviors and physical requirements. Through a combination of ITIAS interactive analysis and mathematical modeling, the study proposes a framework for developing furniture that supports privacy protection, dynamic updates, and better engagement in art education. The findings emphasize the importance of incorporating ergonomic, aesthetic, and technological considerations to improve teaching and learning outcomes in art classrooms.